An Application of Cellular Manufacturing System for a Refrigerator Door Gaskets Processing Improvement: a Case Study - Kaweegitbundit, Parinya; Jaemsang, Orajid (International Journal of Engineering and Technology, 2018)
This paper aims to study the processing improvement on electrical industry in Thailand. The case study of manufacturer is an electrical part assembly factory. The main product of this manufacturer is a refrigerator door gasket. In the past several month, that factory had a high production cost and the productivity on the production line is quite down. Therefore, this paper applies the processing improvement approach that is cellular manufacturing system with the ECRS principal for the production line. The results illustrate that the propose improvement approach is more efficient for a refrigerator door gaskets production line.Â Â